The lived experiences of children living on the streets of Hillbrow - Chris Myburgh; Aneesa Moolla; Marie Poggenpoel (AOSIS, 2015)
Background: The effects of daily abuse and hardship on the streets lead to poor mental health in children living on the streets, resulting in them choosing ineffective and self-destructive coping strategies that impact their physical health and overall sense of wellbeing. The facilitation of the mental health of children living on the streets who are subjected to daily threats to their survival is thus crucial. Objectives: The aim of this research was to explore and describe the lived experiences of children living on the streets of Hillbrow, Johannesburg. Method: The research design was qualitative, exploratory, descriptive and contextual. A purposive sample was selected through a temporary shelter in Johannesburg, Gauteng, South Africa and consisted of 14 male children living on the streets. Data were collected using drawings, in-depth phenomenological interviews and field notes. The central interview opening statement was: 'Tell me about your life on the street'. Results: The results obtained indicated that children living on the streets are threatened, exploited and exposed to physical, sexual and emotional abuse on a daily basis by the community, the authorities and other street dwellers. This leads to feelings of sadness, fear, anxiety, misery, despair, hopelessness, helplessness and suicide ideation, which in turn lead to drug abuse and criminal activities. In contrast, positive feelings of sympathy for other children living on the streets emerged and these children also displayed perseverance, resilience and a striving for autonomy. Conclusion: Street life exposes children to a variety of experiences, both positive and negative. A striving after autonomy is clearly depicted by these children, who are able to tap into a range of responses, both on- and off-street.